2017
DOI: 10.1021/acs.inorgchem.6b02944
|View full text |Cite
|
Sign up to set email alerts
|

The Planar Cyclooctatetraene Bridge in Bis-Metallic Macrocycles: Isolating or Conjugating?

Abstract: A minor modification of the reported procedure for the synthesis of a corrole dimer that is fused by the cyclooctatetraene (COT) unit, (Htpfc)COT, allowed for its isolation in 18% yield. Of the two redox isomers that this interesting macrocycle does form, the current focus is on the reduced form, in which each subunit resembles that of monomeric corroles with a trianionic N coordination core. The corresponding bis-gallium(III) complex was prepared as an entry into the potentially rich coordination chemistry of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 71 publications
2
20
0
Order By: Relevance
“…Dimer 7 was probably formed via 2–2′ linked dimer, which has been later confirmed by preparing 7 from the isolated 2–2′ linked dimer via oxidation with DDQ (vide infra). Later, Gross and co‐workers reported a modified synthesis of 7 by heating 1 a in the same solvent at 200 °C in the air …”
Section: Singly Linked Corrole Dimers and Oligomersmentioning
confidence: 99%
See 3 more Smart Citations
“…Dimer 7 was probably formed via 2–2′ linked dimer, which has been later confirmed by preparing 7 from the isolated 2–2′ linked dimer via oxidation with DDQ (vide infra). Later, Gross and co‐workers reported a modified synthesis of 7 by heating 1 a in the same solvent at 200 °C in the air …”
Section: Singly Linked Corrole Dimers and Oligomersmentioning
confidence: 99%
“…Recently Gross et al. reported the gallium(III) metalation of 7 with GaCl 3 in pyridine to afford gallium(III) complex 7GaPy 2 and 7GaPy 4 , whose electronic conjugation through the cyclooctatetraene bridge was modulated by the axially coordinated pyridines and their redox state …”
Section: Doubly Linked Corrole Dimersmentioning
confidence: 99%
See 2 more Smart Citations
“…8,9,10 It has been demonstrated both experimentally and computationally that COT can be planarized through annulation with strained rings or by incorporation into a rigid planar π-system, forcing the central COT moiety to adopt a planar geometry with alternating single and double bonds. 1,4,8,9,[11][12][13][14][15][16][17][18][19][20][21][22][23][24] Merino and coworkers showed that an alternative approach for planarizing COT to adopt a D 4h symmetric structure is substitution of four alternating carbons with heavier group 14 elements (Si, Ge, and Sn). 25 Based on statistical analysis of X-ray data of 47 COT rings, Dominikowska and Palusiak further found that COT planarizes when acting as an effective π-type ligand in various organometallic complexes.…”
Section: Introductionmentioning
confidence: 99%